Small fish in a big pond: an architectural approach to users privacy, rights and security in the age of big data - Angelopoulos, Spyros; McAuley, Derek; Merali, Yasmin; Mortier, Richard; Price, Dominic (2016)
We focus on the challenges and issues associated with Big Data, and propose a novel architecture that uses the principles of Separation of Concerns and distributed computing to overcome many of the challenges associated with storage, analysis and integrity. We address the issue of asymmetrical distribution of power between the originators of data and the organizations and institutions that make use of that data by taking a systemic perspective to include both sides in our architectural design, shifting from a customer-provider relationship to a more symbiotic one in which control over access to customer data resides with the customer. We illustrate the affordances of the proposed architecture by describing its application in the domain of Social Networking Sites, where we furnish a mechanism to address problems of privacy and identity, and create the potential to open up online social networking to a richer set of possible applications.